1935
DOI: 10.1084/jem.62.5.697
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Theory of the Precipitin Reaction

Abstract: In the first paper of this series (1) 1 it was shown that the precipitin reaction might be considered the resultant of a series of competing bimolecular reactions, the quantitative outcome of which depended on the relative proportions in which the components were mixed. It was thus found possible to express the entire course of the precipitin reaction between a specific polysaccharide and its homologous antibody by simple equations derived from the mass law. In the second paper of the series (2) it was shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0
1

Year Published

1937
1937
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 355 publications
(116 citation statements)
references
References 8 publications
(25 reference statements)
9
106
0
1
Order By: Relevance
“…It has previously been shown that typical instances of the precipitin reaction could be quantitatively described by means of equations derived from the law of mass action (4)(5)(6)(7)(8). These equations and the significance of their constants, as well as empirical equations which in some instances fitted the data even more closely, were discussed in the preceding paper (8) and are therefore given only in their applied form in the tables in the present paper.…”
Section: (From the Departments Of Biological Chemistry And Medicine mentioning
confidence: 91%
See 1 more Smart Citation
“…It has previously been shown that typical instances of the precipitin reaction could be quantitatively described by means of equations derived from the law of mass action (4)(5)(6)(7)(8). These equations and the significance of their constants, as well as empirical equations which in some instances fitted the data even more closely, were discussed in the preceding paper (8) and are therefore given only in their applied form in the tables in the present paper.…”
Section: (From the Departments Of Biological Chemistry And Medicine mentioning
confidence: 91%
“…Tg suspensions were made and injections carried out as described in (6). Rabbits were injected with 1 to 5 rag.…”
Section: Expf+rimentalmentioning
confidence: 99%
“…That the actual plasma antibody is capable of precipitating more antigen in vivo than in vitro seems unlikely, since the precipitin reaction performed in vitro involves refrigeration as well as incubation, and it is well known that refrigeration causes a small but significant increase in the total amount of precipitate obtained (see, for example, Heidelberger & Kendal, 1935). Moreover, in passively immunized animals the vitro/vivo ratio does approximate to unity.…”
Section: Discussionmentioning
confidence: 99%
“…This secondary or anamnestic response to a non-specific stimulus has not been confirmed by accurate quantitative serological methods. For example, Heidelberger & Kendal (1935) were unable to obtain any increase in the titre of rabbit antiovalbumin serum by injecting large amounts of horse serum, and van der Scheer, Bohnel, Clarke & Wyckoff (1942) can have had any significant effect in increasing the amount of available antibody, since the quantitative effect of 'non-plasma antibody' on antigen elimination is frequently considerably greater than that of plasma antibody, and it is unlikely that the amounts of additional antibody required could be made available by the lymphocytes in the short time involved. Moreover, the lymphocytopenia accompanying injection of cortisone had no effect on the vitro/vivo ratio and did not increase the circulating antibody titre of the serum.…”
Section: Discussionmentioning
confidence: 99%
“…ually absorbed with a homologous antigen, a certain portion remains in the supernate as one approaches the equivalence point (21,22). These antibodies no longer precipitate upon the further addition of increments of antigen.…”
Section: The Effect Of Concentration On the Precipitinmentioning
confidence: 99%